The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12974-020-01931-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term and brain-wide colonization of peripheral bone marrow-derived myeloid cells in the CNS

Abstract: Background Microglia, the primary resident myeloid cells of the brain, play critical roles in immune defense by maintaining tissue homeostasis and responding to injury or disease. However, microglial activation and dysfunction has been implicated in a number of central nervous system (CNS) disorders, thus developing tools to manipulate and replace these myeloid cells in the CNS is of therapeutic interest. Methods Using whole body irr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 93 publications
1
42
0
Order By: Relevance
“…In particular, long-term effects of microglia replacement are now not well understood. To that end, a recent study found subtle changes in transcriptional, histological, and behavioral features of mice with high CDMC chimerism (16). It is further possible that CDMCs mount a different immune response to CNS pathology than microglia.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, long-term effects of microglia replacement are now not well understood. To that end, a recent study found subtle changes in transcriptional, histological, and behavioral features of mice with high CDMC chimerism (16). It is further possible that CDMCs mount a different immune response to CNS pathology than microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Following recovery, we explored co-localization of MAC2 expression in GFP+ cells in the adult mouse brains of long-term GFP BM chimeric mice and long-term GFP BM chimeric mice that underwent colony-stimulating factor 1 receptor inhibitor (CSF1Ri)-induced myeloid cell depletion and repopulation (~6 months following CSF1Ri treatment and CNS engraftment) (Figure 2a). In a previous study, we demonstrated that irradiation/BM transplant followed by CSF1Ri treatment results in substantial replacement of the microglial compartment with BM-derived monocytes (Hohsfield et al, 2020), providing a model to evaluate long-term and brain-wide BM-derived monocyte/macrophage engraftment.…”
Section: Mac2 Is a Specific And Long-lasting Marker For Bone Marrow-d...mentioning
confidence: 99%
“…The recent wave of studies characterizing microglia at single-cell resolution indicate extensive transcriptional heterogeneity during development and disease, with a more homogeneous population evident in the homeostatic adult brain [5-7, 23, 24]. If an empty niche is available in the tissue myeloid compartment, cues from the local microenvironment can reprogram infiltrating bone marrow-derived monocytes or ontogenically foreign macrophages into microglialike phenotypes [25][26][27][28][29][30]. The extent of transcriptional reprogramming appears to depend on the yolk-sac or hematopoietic origin of the cell in question [8,26], at least in the CNS, where the adult resident macrophage population (e.g., microglia) derives from yolksac erythromyeloid progenitors [31][32][33][34].…”
mentioning
confidence: 99%